The cyber citizen's guide through the legal jungle : Internet law for your professional online presence - Butler, Joy R. (Sashay Communications, 2010)
If you actively use the internet to advance your business and professional endeavors, you are a cyber citizen and this book is for you. As a good cyber citizen, you want to stay legal online and protect your online interests. The Cyber Citizen's Guide Through the Legal Jungle addresses legal issues that arise during each step of establishing and maintaining your professional online presence whether you blog, podcast, operate a website, publish an email newsletter, host a fan site, or offer original content on a social networking site.